The Student''s scientific society is the axiological potential of modern higher medical education - S. G. Zabolotnaya (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2013)
The axiological potential of the students' work in the Students' Scientific Society (SSS) is deal with in this article. The conditions of the pedagogical process, specificity of the pedagogical guidance, and early involvement of medical students in the work of SSS are described.